COVID-19: Factors Associated with Dental Students' Fear of Infecting their Relatives as a Result of Clinical Practice - Marcos de Oliveira Júnior; Fernanda Costa Souza; Rayanne Camylle Nunes Gomes; Fabiana Vargas-Ferreira; Flávio Freitas Mattos; Mauro Henrique Nogueira Guimarães de Abreu; Renata de Castro Martins (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the factors associated with the fear of dental students infecting their relatives with COVID-19 as a result of clinical practice. Material and Methods: Online questionnaires were sent by e-mail and social media to dental students from a Brazilian School of Dentistry. The outcome was "fear of infecting the family." The independent variables were sociodemographic data, personal protective equipment use, adoption of infection control measures, and knowledge and feelings about the pandemic and the future of Dentistry. Data analysis used Pearson's Chi-square and Fisher's exact tests (p≤0.05). Results: With 65 participants, the prevalence of fear was 61.5%. Measures to prevent COVID-19, such as frequent hand cleansing (p=0.028) and avoiding the use of aerosol-generating instruments (p=0.027), not having or not knowing if they have been infected by the disease (p=0.038), and feelings of more significant anxiety during the pandemic period (p=0.047), and that Dentistry will undergo major post-pandemic changes (p=0.020) were associated with fear. Conclusion: Changes in behavior about biosafety and feelings of anxiety and uncertainty about the disease were associated with the dental students' fear of infecting their relatives with COVID-19 as a result of clinical practice.